Physical activity and emotional intelligence among undergraduate students: a correlational study - Acebes-Sánchez, Jorge (BMC Public Health, 2019)
BACKGROUND: Physical activity (PA) can be a mechanism that develops emotions. Emotional intelligence (EI) is related to significant public health and psychological benefits. However, there is little information about the relationships between PA and EI dimensions: emotional attention, clarity, and repair. This study examined the possible relationships between these variables in undergraduate students from Madrid. As a secondary aim, sex differences in PA domains and EI dimensions were examined. METHODS: A total of 2960 (21.34 ± 4.34 years) undergraduate students from Madrid (Spain) fulfilled the Trait Meta-Mood Scale (TMMS-24) and Global Physical Activity Questionnaire (GPAQ). We used a MANOVA to compare EI and PA levels according to sex. Different linear regressions were conducted to calculate the PA and age prediction power based on EI. RESULTS: We found a significant association between EI dimensions and PA levels, although these relationships were small. Fully adjusted linear regression showed that sex and leisure-time PA (LTPA) were associated of emotional attention (r(2)(c) = .025). Sex, age, and LTPA were associated of emotional repair (r(2)(c) = .024). There were statistically significant differences in EI by sex (p ≤ .001; η(2)(p =) .039), with higher scores in emotional attention for women (p ≤ .001) and emotional clarity (p ≤ .001) and repair (p ≤ .001) for men. PA levels differed according to sex (p ≤ .001; η(2)(p =) .038). Men show higher scores in LTPA levels (p = .002) and occupational PA (p ≤ .001). CONCLUSIONS: Undergraduate students with higher levels of LTPA showed a better score on EI, specifically in emotional attention and emotional repair. However, these associations and the predictive power of LTPA regarding emotional attention and emotional repair were weak. Men engaged in more LTPA and occupational PA and had higher emotional clarity and emotional repair than women. However, women had higher emotional attention.